2022
DOI: 10.1021/acs.inorgchem.2c00670
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Catalytic Transfer Hydrogenation for Furfural Using Single Ni Atom Catalysts Anchored to Nitrogen-Doped Graphene Sheets

Abstract: Catalytic transfer hydrogenation (CTH) of α,β-unsaturated aldehydes using single metal atom catalysts supported on nitrogen-incorporated graphene sheet (M–N x -Gr) materials has attracted increasing attention recently, yet the reaction mechanism remains to be explored. Compared to the Ni–N4-Gr model in which the dissociation of isopropanol is highly unfavorable as a result of steric hindrance and inertness of the Ni–N4 site embedded in graphene, the Ni–N3 site in Ni–N3-Gr is more active and facilitates the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 71 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…Possible reaction mechanisms for hydrogenation of furfural over metallic sites in the presence of molecular hydrogen as well as hydrogen sacrificial agent, e.g., ethanol, have been proposed earlier. , Similarly, the possible reaction mechanism for the conversion of FA to EL in liquid ethanol is also reported and few reaction pathways through formation of various intermediates were suggested. , Recently, the role of hydrotalcite originated basic sites in the adsorption and activation of the carbonyl group of furfural is reported. The surface basic sites of hydrotalcite-derived mixed oxide in close proximity with active metal sites are capable of having interaction with the π* acceptor orbital of carbonyl group, which consequently leads to the enhanced reactivity of the carbonyl group .…”
Section: Resultsmentioning
confidence: 97%
“…Possible reaction mechanisms for hydrogenation of furfural over metallic sites in the presence of molecular hydrogen as well as hydrogen sacrificial agent, e.g., ethanol, have been proposed earlier. , Similarly, the possible reaction mechanism for the conversion of FA to EL in liquid ethanol is also reported and few reaction pathways through formation of various intermediates were suggested. , Recently, the role of hydrotalcite originated basic sites in the adsorption and activation of the carbonyl group of furfural is reported. The surface basic sites of hydrotalcite-derived mixed oxide in close proximity with active metal sites are capable of having interaction with the π* acceptor orbital of carbonyl group, which consequently leads to the enhanced reactivity of the carbonyl group .…”
Section: Resultsmentioning
confidence: 97%
“…Afterward, a computational study on the reaction mechanisms of furfural hydrogenation into FAL on nitrogen-doped graphene sheets-supported Ni SACs (Ni–N x –Gr) has been reported. 45 Ni–N 3 –Gr configuration was advantageous over the Ni–N 4 sites for the formation of *H with isopropanol. Two competitive pathways involving the subsequential adsorption or desorption of the isopropanol and furfural were considered and calculated.…”
Section: (Hemi)cellulose-derived Feedstocksmentioning
confidence: 99%
“…To investigate the reaction mechanism of furfural transfer hydrogenation to furfuryl alcohol, Wang et al calculated the catalytic process for furfural hydrogenation over Ni 1 /N x -Gr catalyst using isopropanol as the H donor. 85 They found that the configurations and electronic structures of isopropanol and furfural on Ni 1 /N 3 -Gr with Ni−N 3 sites were active, while Ni 1 / N 4 -Gr with Ni−N 4 sites were inert. The difference was attributed to the lower steric hindrance and inertness of the Ni−N 3 sites.…”
Section: Furfural Conversionmentioning
confidence: 99%